미니 산업단지의 입지적합성 평가 연구: 수도권을 중심으로 - 이현주; Hyeon-joo Lee; 최대식; Dae-sik Choi; 송영일; Youngil Song; 이은엽; Eun-yeob Lee; 김태균; Tae-gyun Kim; 곽병조; Byoung-jo Kwak; et al. (한국경제지리학회지, 2020)
최근 도시내 기업입지수요가 증가하나 도시에서 넓은 부지확보는 어려우므로 소규모 ‘미니산업단지’ 형태가 미래형 산단 유형으로 적절할 것이다. 수도권지역을 대상으로 저활용되는 부지를 잠재적 개발후보지로 가정하고 입지적합성 평가지표를 적용하여 시범 평가해 보았다. 전문가와 기업체설문을 통해 지표간 중요도를 분석한 후 이를 가중치로 하여 1∼4등급 후보지를 구분하였다. 1등급 후보지에 영향을 미친 지표로는 기업체 가중치를 적용한 경우 교통접근성과 도시서비스 여건인 반면 전문가 가중치 적용경우 첨단·지식산업 및 대학·연구소로 나타났다. GIS 분석 결과 서울-경기남부축과 서울-경기남서부축이 가장 우수한 미니산단 입지지역으로 도출되어 기형성된 지식산업집적지가 향후에도 경쟁력있는 산업지역으로 인식되는 것으로 조사된다. Recently, the demand for corporate location in the city is increasing. Due to the difficulty of finding a large site in the city, the small-scale ‘mini-industrial complex’ would be appropriate as a future industrial complex type. In response to this, site suitability indicators was prepared and applied to the metropolitan area as a pilot. To this end, the under-utilized site were assumed as potential candidates for development. After analyzing the importance among indicators through a questionnaire from experts and companies, this was applied as a weight. As a result, candidate sites ranging from Grade 1 to Grade 4 were derived. The indicators that had a great influence on the location identified as a Grade 1 were transport accessibility and urban service conditions when the company weight was applied, whereas advanced knowledge industry and university/research center when applying expert weight. The Seoul-south axis and southwest axis of Gyonggi-Do were identified as the most excellent mini-industrial complex locations among the Seoul metropolitan areas. It means that the already formed knowledge industry clusters will be recognized as competitive future industrial locations.